Ionic Channels as Potential Therapeutic Targets for Erectile Dysfunction: A Review - Anderson Fellyp Avelino Diniz; Rafael Carlos Ferreira; Iara Leão Luna de Souza; Bagnólia Araújo da Silva (Frontiers Media S.A., 2020)
Erectile dysfunction (ED) is a prevalent condition, especially in men over 40 years old, characterized by the inability to obtain and/or maintain penile erection sufficient for satisfactory sexual intercourse. Several psychological and/or organic factors are involved in the etiopathogenesis of ED. In this context, we gathered evidence of the involvement of Large-conductance, Ca2+-activated K+ channels (BKCa), Small-conductance, Ca2+-activated K+ channels (SKCa), KCNQ-encoded voltage-dependent K+ channels (KV7), Transient Receptor Potential channels (TRP), and Calcium-activated Chloride channels (CaCC) dysfunctions on ED. In addition, the use of modulating agents of these channels are involved in relaxation of the cavernous smooth muscle cell and, consequent penile erection, suggesting that these channels are promising therapeutic targets for the treatment of erectile dysfunction.